La simulación de contratos individuales de trabajo en el Ecuador. - Morocho Betancourt, María Fernanda (2023)
The violation of workers' rights occurs commonly in Ecuador, due to various factors and means. Hence, after the promulgation of the 2008 Constitution, it has represented a greater protection of guardianships and rights in favor of workers, because the Fundamental Charter alludes to the prohibition of all forms of labor precariousness and sanctions simulation, since that would represent a non-existent legal relationship that is used by the employer based on deception. The objective of this research is to analyze the simulation of individual work contracts in Ecuador. The methodology used in this study is non-experimental, descriptive and field. We work with a random probabilistic sample, with personnel belonging to the labor code in different institutions in the city of Riobamba. Once the study has been carried out, it can be concluded that the simulation of individual work contracts in Ecuador was born with outsourcing, a legal figure that was previously applied in labor relations between employers and workers; It has been possible to establish that this legal figure is not properly regulated and sanctioned in other infra-constitutional norms, therefore, the existence of a legal vacuum that has generated violation of constitutional rights and principles.